The investigation of fetal dose for mantle field irradiation of Hodgkin’s disease - Karaçam, Songül Çavdar; Öksüz, Didem Çolpan; Koca, Ayşe; Günhan, Basri; Çepni, İsmail and Çepni, Kimia and Beşe, Nuran (Cerrahpaşa Medical Journal, 2019)
Objectives: Hodgkin’s disease, breast and servical cancer, malignant melanoma, and leukaemia are the most frequenly diagnosed malignant disorders during pregnancy. Radiotherapy during pregnancy might cause harm to the developing fetus. Methods: The aim of this work was to estimate the radiation dose delivered to the fetus in a pregnant patient during the mantle field irradiation for Hodgkin’s disease. Radiation dose to fetus was estimated from phantom measurements using thermoluminescence dosimeters. Phantom measurements were performed by simulating the treatment conditions on an anthropomorphic phantom. Results: Thermoluminescent dosimeters(TLDs) were placed in the phantom 41, 44, 46.5 and 49.5 cm from the centre of the treatment field. Two TLDs were placed on the surface of the phantom. The estimated total dose to the all TLDs ranged from 8.8 to 13.8 for treatment with Co-60, and from 8.2 to 12.3 cGy for 4 MV photons. Conclusion: These results show that it is a risk of developing malinancies to treat a pregnant patient with treatment conditions. The use of supplemental fetal-shielding can reduce the fetal exposure.